2000
DOI: 10.1309/rev9-fdtm-5ngc-hbwy
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis C Virus RNA Sequences in B-Cell Non-Hodgkin Lymphoma

Abstract: Serologic testing shows that hepatitis C virus (HCV) may have a role in the pathogenesis of B-cell non-Hodgkin lymphomas (B-cell NHLs). We tried to demonstrate HCV RNA sequences in paraffin-embedded tissue from B-cell NHLs by reverse-transcription double polymerase chain reaction (RT-PCR) and Southern blotting. We studied 31 consecutive cases of B-cell NHLs; lymph nodes from 32 patients with diseases other than B-cell NHL were negative controls. Positive-strand HCV RNA was tested with primers for the 5' untran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
2
20
0
1
Order By: Relevance
“…Besides, an important association has been demonstrated between HCV and lymphoproliferative disorders. Many studies have shown an increased prevalence of HCV infection in patients with B-cell non-Hodgkin's lymphoma (B-NHL), and the prevalence is between 9% and 32% [2][3][4][5][6][7][8][9][10]. In these studies, HCV has been tested serologically, but today the prevalence of HCV in lymphoproliferative disorders is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, an important association has been demonstrated between HCV and lymphoproliferative disorders. Many studies have shown an increased prevalence of HCV infection in patients with B-cell non-Hodgkin's lymphoma (B-NHL), and the prevalence is between 9% and 32% [2][3][4][5][6][7][8][9][10]. In these studies, HCV has been tested serologically, but today the prevalence of HCV in lymphoproliferative disorders is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, mutations in TP53, CTNNB1, and BCL6 were also identified in peripheral blood mononuclear cells (PBMC) of HCV-positive patients (12), although only about 10% of PBMC are B cells. As TP53 is a tumor suppressor gene and BCL6 and CTNNB1 are protooncogenes, mutations in these genes might be of pathogenetic relevance.Regarding the reported mutagenic effect of HCV, it should be mentioned that it is still controversially discussed whether HCV indeed infects B cells and induces mutations by a hit-and-run mechanism, or whether the effects seen are due to the binding of HCV to costimulatory receptors expressed on the surface of B cells, such as CD81 (17)(18)(19)(20)(21)(22)(23)(24).In the present work, we aimed to clarify whether the mutagenic effect of HCV on TP53, CTNNB1, and BCL6 is detectable in B cells of chronically HCV-infected patients, and hence might represent a main factor for B-cell lymphoproliferative diseases in such patients. …”
mentioning
confidence: 99%
“…Regarding the reported mutagenic effect of HCV, it should be mentioned that it is still controversially discussed whether HCV indeed infects B cells and induces mutations by a hit-and-run mechanism, or whether the effects seen are due to the binding of HCV to costimulatory receptors expressed on the surface of B cells, such as CD81 (17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…MC is considered to be a benign B-cell proliferative disorder with clonal expansion of distinct B cells that can eventually turn into frank B-cell malignancy (3). Indeed, several groups have shown an increased incidence of B-cell nonHodgkin's lymphoma (B-NHL) in patients with chronic HCV infection (4), and an increased prevalence of HCV infections in patients with B-NHL has been reported (5,6). The hypothesis of an association between B-NHL and HCV infection is further supported by the observation that eradication of HCV by treatment with IFN-a and ribavirin could induce complete remission of splenic lymphomas with villous lymphocytes in seven of nine patients with chronic hepatitis C, whereas the same treatment had no effect in six patients with lymphomas who were HCV negative (7).…”
mentioning
confidence: 99%